Diseño de logotipo y realización de manual de identidad visual para la marca de jabones “La Pompa” - Vasquez Amat y Leon, Paola (2020)
Throughout this document we are going to find a report on the creation of a brand of personalized handmade soaps called La Pompa, which is graphically expressed in a brand book. It describes the process of creating the identity of the brand and the graphic guidelines that reflect its personality and provide it with the necessary coherency to strengthen its remembrance, loyalty and positioning in the Lima market.